Ly49 Receptors and MHC-I Interactions, and their Implications in Cancer Immunosurveillance - Tu, Megan Mai (Université d'Ottawa / University of Ottawa, 2017)
Natural killer cells are part of the innate immune response, and get their name ‘natural killer’ due to their unique ability to recognize and kill aberrant cells without prior sensitization. The Ly49 receptors on NK cells are involved in both their education process and mediating their ability to recognize aberrant cells. Virally-infected and tumor cells have been shown to exhibit decreased levels of MHC-I on their cell surface. As MHC-I is expressed on all nucleated cells, the Ly49 receptors on NK cells recognize this loss of MHC-I on the surface as a kill signal, leading to direct cytotoxicity through the release of perforin and granzymes. This recognition process by NK cells is termed “missing-self.” The interactions between MHC-I and Ly49 receptors are integral to NK cell function. The response of the NK cell to cells which it encounters is dependent on a balance of activating and inhibitory receptors. This signal in turn is dependent on the engagement and interactions of various ligands, such as MHC-I, by the activating and inhibitory Ly49s on the NK cells. In this compilation of my three main research projects, the interactions and binding capacity between the different MHC-I molecules and different members of the Ly49 receptor family are explored. In addition, the importance of the Ly49 receptors in NK cell-mediated cancer immunosurveillance is studied.
Keywords: Cancer; Immunology